Synthesis and Spectroscopic and Antimicrobial Studies of Schiff Base Metal Complexes Derived from 2-Hydroxy-3-methoxy-5-nitrobenzaldehyde. (17th November 2014) - Joshi, K. R.; Rojivadiya, A. J.; Pandya, J. H.
Abstract : Two new series of copper(II) and nickel(II) complexes with two new Schiff base ligands 2-((2, 4-dimethylphenylimino)methyl)-6-methoxy-4-nitrophenol and 2-((3, 4-difluorophenylimino)methyl)-6-methoxy-4-nitrophenol have been prepared. The Schiff base ligands were synthesized by the condensation of 2-hydroxy-3-methoxy-5-nitrobenzaldehyde with 2, 4-dimethylaniline or 3, 4-difluoroaniline. The ligands and their metal complexes have been characterized by IR, 1 H NMR, mass and electronic spectra and TG analysis. The Schiff base ligands and their metal complexes were tested for antimicrobial activity against Gram positive bacteria Staphylococcus aureus, and Streptococcus pyogenes and Gram negative bacteria Escherichia coli, and Pseudomonas aeruginosa and fungus Candida albicans, Aspergillus niger, and Aspergillus clavatus using Broth Dilution Method.